2019
DOI: 10.1016/j.neuron.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 2b Regulates Sleep-Circuit Formation in the Drosophila Central Brain

Abstract: The fan-shaped body (FB) neuropil in the Drosophila brain central complex (CX) controls a variety of adult behaviors, including navigation and sleep. How neuronal processes are organized into precise layers and columns in the FB and how alterations in FB neural-circuit wiring affect animal behaviors are unknown. We report here that secreted semaphorin 2b (Sema-2b) acts through its transmembrane receptor Plexin B (PlexB) to locally attract neural processes to specific FB laminae. Aberrant Sema-2b/ PlexB signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…These cells invaded the CA, the peduncle, and ß and ß’ lobes as well as α and α’ lobes of the MB (Figure 5h, j–n). In contrast, we were not able to trace the neurons that invaded the fan‐shaped body, but according to their arborization pattern in the dFB, they must belong to tangential neurons that have cell bodies in the SLP, axonal arborizations in the 6th layer of the fan‐shaped body, and dendrites in the SMP (Donlea et al., 2018; Xie et al., 2019). These dFB neurons have been described by several previous studies due to their prominent role in sleep; they are revealed by the R23E10‐Gal4 driver (Donlea et al., 2014, 2018; Ni et al., 2019) and are also called ExFl2 neurons (Xie et al., 2019).…”
Section: Resultsmentioning
confidence: 98%
“…These cells invaded the CA, the peduncle, and ß and ß’ lobes as well as α and α’ lobes of the MB (Figure 5h, j–n). In contrast, we were not able to trace the neurons that invaded the fan‐shaped body, but according to their arborization pattern in the dFB, they must belong to tangential neurons that have cell bodies in the SLP, axonal arborizations in the 6th layer of the fan‐shaped body, and dendrites in the SMP (Donlea et al., 2018; Xie et al., 2019). These dFB neurons have been described by several previous studies due to their prominent role in sleep; they are revealed by the R23E10‐Gal4 driver (Donlea et al., 2014, 2018; Ni et al., 2019) and are also called ExFl2 neurons (Xie et al., 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Here, we have used temporally restricted genetic manipulations to show that inc acts during neuronal development to ultimately impact sleep in adulthood. While many genes are known to act in adults to impact sleep, developmental mechanisms underlying sleep regulation have only recently gained attention ( Chakravarti Dilley et al, 2020 ; Gong et al, 2021 ; Iwasaki et al, 2021 ; Xie et al, 2019 ). Our results underscore the importance of unbiased temporal genetic manipulations to define critical periods through which genes impact sleep, and suggest that genes may influence sleep through unappreciated developmental mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cell intrinsic biomechanical properties are essential for migrating cells to negotiate tight interstitial spaces while maintaining traction on substrate surfaces; in this context, balanced Plexin-B2 activity appeared to be crucial, as both Plexin-B2 deficiency or forced overexpression impeded GBM spread in intracranial transplants. This echoes the requirement for balanced levels of semaphorin/plexin activity during neurodevelopment, where both loss- and gain-of-function conditions can result in similar axon guidance defects 55 .…”
Section: Discussionmentioning
confidence: 62%